Experience of prenatal consultation in Zaporizhzhia region over the 2011-2015 years - N. V. Avramenko; H. A. Lomeyko; O. A. Nikiforov; O. S. Sukhonos (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Congenital malformations are one of the main causes of high infant mortality and disability from childhood. Medical and genetic counseling is an important integral part of prenatal diagnosis.